Tinjauan Naratif: Bawang Hitam (Allium sativum L.) sebagai Agen Nefroprotektif dan Perubahan Berat Badan pada Model Nefrotoksisitas Gentamisin - Jauharotul Firdausiyah; Riana Putri Rahmawati; Intan Adevia Rosnarita (KOLONI, 2026)
Black garlic is the product of fermenting fresh garlic (Allium sativum L.), which is rich in bioactive compounds such as S-allyl cysteine, polyphenols, and flavonoids with antioxidant and anti-inflammatory activities. These compounds have potential as nephroprotectors against gentamicin-induced kidney damage. This narrative review seeks to consolidate evidence regarding black garlic's nephroprotective mechanisms, dose-response patterns in gentamicin-induced nephrotoxicity, and its impact on body weight variations. Literature was sourced from PubMed, ScienceDirect, Google Scholar, and Sinta, covering the publication period 2020–2025, using the keywords black garlic; nephroprotective; nephrotoxicity; and Allium sativum. The results of the review indicate that S-allyl cysteine and flavonoids act by inhibiting ROS and increasing SOD, GPx, and CAT; suppressing NF-kB accompanied by a decrease in TNF-alpha and IL-6; regulation of the Bcl-2/Bax ratio along with caspase-3 suppression, plus enhanced renal hemodynamics through nitric oxide.